Uniform cobalt nanoparticles embedded in nitrogen-doped graphene with abundant defects as high-performance bifunctional electrocatalyst in overall water splitting. (8th June 2022) - Chu, Wenhui; Yu, Yuan; Sun, Dongfeng; Qu, Yanning; Meng, Fangyou; Qiu, Yingying; Lin, Songmin; Huang, Linyin; Ren, Jie; Su, Qingmei; Xu, Bingshe
Abstract: Co nanoparticles with uniform size (about 5 nm) embedded in N -doped graphene (Co-NG) were explored in this work. The introduction of a second carbon source of citric acid during synthesis prevented the Co atoms from growing up, thus regulating the size of the cobalt nanoparticles. N atoms in N -doped graphene had more lone-pair electrons, making it easier to capture electrons from hydrated ions, and facilitating the dynamics procedure of HER. Furthermore, N dopant rendered larger positive charge density on the adjacent carbon atoms, which was conducive to OER and HER. At 10 mA cm −2 of the current density, the Co-NG/CC catalyst's overvoltage of HER was 78 mV, approaching that of 20% Pt/C (59 mV), an efficient precious metal electrocatalyst for HER, while its overvoltage of OER was about 225 mV, 12.5% lower than that of RuO2 (257 mV, a common precious metal oxide OER electrocatalyst). In addition, this Co-NG/CC composite bifunctional catalyst displayed good electrochemical stability in alkali solution and might be designed as a dual-function catalyst in the application of overall water splitting. The cell voltage of Co-NG/CC//Co-NG/CC was only 1.66 V, approaching to that of full precious metal cell of Pt/C//RuO2 (1.52 V), and revealing the good commercial application prospects of this composite bifunctional catalyst. Graphical abstract: Image 1 Highlights: Early introduction of citrate modulated the size of the Co, causing larger active area and better catalytic activity. N dopant in graphene and Co–N bond accelerate the HER and OER dynamics process, improving the catalytic activity. Good intrinsic activity of Co and the synergistic role of GO make the catalyst good catalytic activity and stability.